Characterization of the complete mitochondrial genome of the moss, Myurella julacea (Schwägr.) Schimp. (Bryidae, Theliaceae). Issue 3 (4th March 2021) - Jung, Jin-Woo; Han, Yeong-Deok; Yoon, Young-Jun
Abstract: The present study reports the complete mitochondrial genome of Myurella julacea (Schwägr.) Schimp. (GenBank accession number MT850126); the genome size was 104, 979 bp. The gene arrangement was found to be similar to that in other bryophytes, and the genome consisted of 40 protein-coding genes (PCGs), 3 ribosomal RNAs (rRNAs), and 24 transfer RNAs (tRNAs). The phylogenic relationship was analyzed by construction of a phylogenetic tree based on the mitogenome of M . julacea and 25 other bryophytes publicly available in GenBank. The complete mitogenome of M. julacea is expected to provide insights into the evolution of species belonging to the order Hypnales.